Lipids of Platelet-Rich Fibrin Reduce the Inflammatory Response in Mesenchymal Cells and Macrophages - Zahra Kargarpour; Layla Panahipour; Michael Mildner; Richard J. Miron; Reinhard Gruber (2023)
Platelet-rich fibrin (PRF) has a potent anti-inflammatory activity but the components mediating this effect remain unknown. Blood lipids have anti-inflammatory properties. The question arises whether this is also true for the lipid fraction of PRF. To answer this question, lipid fractions of solid and liquid PRF were tested for their potential to lower the inflammatory response of ST2 bone marrow stromal cells and primary bone marrow macrophages exposed to IL1β and TNFα, and LPS, respectively. Cytokine production and the underlying signalling pathway were analysed by RT-PCR, immunoassays, and Western blotting. We report here that lipids from solid and liquid PRF substantially lowered cytokine-induced expression of IL6, CCL2 and CCL5 in ST2 cells. Moreover, the inflammatory response induced by Pam3CSK4, the agonist of Toll-like receptor (TLR) TLR2, was partially reduced by the lipid extracts in ST2 cells. The PRF lipids further reduced the LPS-induced expression of IL1β, IL6 and CCL5 in macrophages at the transcriptional level. This was confirmed by showing the ability of PRF lipids to diminish IL6 at the protein level in ST2 cells and macrophages. Likewise, PRF lipid extracts reduced the phosphorylation of p38 and JNK and moderately decreased the phosphorylation of NFκB-p65 in ST2 cells. These findings suggest that the lipid fraction is at least partially responsible for the anti-inflammatory activity of PRF in vitro.